Vitamin B5 supplementation enhances intestinal development and alters microbes in weaned piglets - Xin Wang; Yan Qin; Jianzhong Li; Pengfei Huang; Yali Li; Jing Huang; Qiye Wang; Huansheng Yang (Animal Biotechnology, 2024)
This study explored the effects of different vitamin B5 (VB5) levels on intestinal growth and function of weaned piglets. Twenty-one piglets (7.20 ± 1.11 kg) were included in a 28-day feeding trial with three treatments, including 0 mg/kg (L-VB5), 10 mg/kg (Control) and 50 mg/kg (H-VB5) of VB5 supplement. The results showed that: Large intestine weight/body weight was the highest in H-VB5 group, Control and H-VB5 groups had significantly higher villus height and villus height/crypt depth than the L-VB5 in the ileum (p < .05). Goblet cells (ileal crypt) and endocrine cells (ileal villus) significantly increased in Control and H-VB5 (p < .05). The H-VB5 group exhibited significantly higher levels of ki67 and crypt depth in the cecum and colon, colonic goblet cells and endocrine cells were both rising considerably (p < .05). Isobutyric acid and isovaleric acid were significantly reduced in the H-VB5 group (p < .05), and there was a decreasing trend in butyric acid (p = .073). At the genus level, the relative abundance of harmful bacteria such as Clostridium_Sensu_Structo_1 Strecto_1, Terrisporbacter and Streptococcus decreased significantly and the relative abundance of beneficial bacteria Turicibacter increased significantly in H-VB5 group (p < .05). Overall, the addition of 50 mg/kg VB5 primarily enhanced the morphological structure, cell proliferation and differentiation of the ileum, cecum and colon. It also had a significant impact on the gut microbiota and short-chain fatty acids.